Contributions to the Knowledge of Mammals in Corum Province, Turkey - Burak Akbaba; Ahmet Karatas; Safak Bulut (Hittite Journal of Science and Engineering, 2017)
A total of 42 mammal species were determined and new records reported for the first time in Çorum Province, Turkey. Field studies were carried between 2009-2010 and 2015-2016. One species of hedgehog and shrew, four bat species, six rodent species, roe deer and three carnivore species were recorded for the first time. We also expanded the known distribution and confirmed the presence of four rodent species Spermophilus xanthophyrmnus, Microtus dogramaci, Mesocricetus brandti and Meriones tristrami in the province. In addition, some information related to the distribution and the habitat associated to some taxon were provided in the study.